2020
DOI: 10.3390/v12111242
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as an Antiviral Agent

Abstract: Curcumin, the primary curcuminoid compound found in turmeric spice, has shown broad activity as an antimicrobial agent, limiting the replication of many different fungi, bacteria and viruses. In this review, we summarize recent studies supporting the development of curcumin and its derivatives as broad-spectrum antiviral agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 81 publications
2
93
0
1
Order By: Relevance
“…An in vivo study on a mouse model with intravaginal HSV-2 showed significant protection against HSV-2 infection due to curcumin administration [ 74 ]. Curcumin exerts its antiviral effects through signaling pathways, such as actin filament organization by replication inhibition in dengue virus and viral hemorrhagic septicemia virus; anti-inflammation and antioxidation activity inhibiting HIV replication; conformation of viral/cellular surface proteins through viral attachment in Zika virus, chikungunya virus, vesicular stomatitis virus, and human respiratory syncytial virus; HSC71 expression induces viral entry block in viral hemorrhagic septicemia virus; NF-κB signaling induce inhibition the replication and viral egress in Influenza A virus and HSV-2 [ 75 ]. We found nine surveys showing curcumin activity against SARS-CoV-2 targets.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study on a mouse model with intravaginal HSV-2 showed significant protection against HSV-2 infection due to curcumin administration [ 74 ]. Curcumin exerts its antiviral effects through signaling pathways, such as actin filament organization by replication inhibition in dengue virus and viral hemorrhagic septicemia virus; anti-inflammation and antioxidation activity inhibiting HIV replication; conformation of viral/cellular surface proteins through viral attachment in Zika virus, chikungunya virus, vesicular stomatitis virus, and human respiratory syncytial virus; HSC71 expression induces viral entry block in viral hemorrhagic septicemia virus; NF-κB signaling induce inhibition the replication and viral egress in Influenza A virus and HSV-2 [ 75 ]. We found nine surveys showing curcumin activity against SARS-CoV-2 targets.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnopharmacology study of Zingiberaceae plants collected in Central Sulawesi, found the application of Curcuma longa to treat the HIV-1 infection. Literature investigation found that Curcuma longa contained curcumin as major compound that has been reported to possess a wide range inhibition of viruses such as dengue virus, herpes virus, and human immunodeficiency virus [ 7 , 17 ]. Therefore, we interest in further testing the other Zingiberaceae plants for antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, curcumin has presented effectiveness against a wide number of viruses, such as the Human Immunodeficiency Virus (HIV), Hepatitis C Virus (HCV), Human Cytomegalovirus (HCMV), Epstein-Barr Virus (EBV), Bovine Herpesvirus 1 (BHV 1), Chikungunya Virus, Ebola Virus, Enterovirus 71 (EV71), Rift Valley Fever Virus (RVFV), Human Norovirus (HuNoV), Respiratory Syncytial Virus (RSV), Fish Viral Hemorrhagic Septicemia Virus (VHSV), and Influenza A Virus (IAV) [23] .…”
Section: Curcumin As An Antiviral Alternative Against Sars-cov-2mentioning
confidence: 99%